THE GUILT IN CASES OF MEDICAL CIVIL LIABILITY AND THE LEGAL NATURE OF ACTIVITY (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
This article presents the topic of medical civil liability, especially in the analysis of its assumption of guilt. The problem of this research is the divergence of understandings about the nature of the activity, whether civil or consumer, and the possibility of presumption of guilt on the part of the medical professional in the event of eventual liability. The general objective is to propose the most appropriate legal diploma to apply in these situations and understand the possibility of presumption of guilt. The specific objectives are: a) to present a general overview of civil liability; b) deepen the discussion of the legal nature by presenting a response to the debate; c) answer the question about the possibility of presuming guilt in cases of medical civil liability. The deductive method is used, starting from the general aspects of civil liability, with the help of bibliographical research in works on the subject.